2015
DOI: 10.1007/s00586-015-4168-7
|View full text |Cite
|
Sign up to set email alerts
|

The presence of stem cells in potential stem cell niches of the intervertebral disc region: an in vitro study on rats

Abstract: To the best of our knowledge, this is the first in vitro study aimed towards determining the existence and characteristics of ISN-SCs, which belong to the MSC family and with greater osteogenic and chondrogenic abilities than BMSCs according to our data. This finding may be of great significance for additional studies that investigate the migration of ISN-SCs into the IVD, and may provide a new perspective on different biological approaches for IVD self-regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 48 publications
(71 reference statements)
3
20
0
Order By: Relevance
“…Our study is based on previous other studies describing the presence of stem cells derived from NP tissue [18, 19, 22, 23, 3032]. However, studies on the cell characteristics and potential of these cells are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study is based on previous other studies describing the presence of stem cells derived from NP tissue [18, 19, 22, 23, 3032]. However, studies on the cell characteristics and potential of these cells are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed contents of medium A and B have been described previously [22]. First, the 2.0 × 10 4 P4 cells in each plate were incubated in induction medium A for 72 h, which was then replaced with maintenance medium B for 24 h. This 96 h induction-maintenance cycle was repeated four times and in the end, cells were incubated in maintenance medium B for 7 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies suggest that the IVD contains a resident stem cell population (Shi et al, 2015; Kraus et al, 2017), however this work was performed in rodents and bovine so it is unclear if the same cell populations will be found in humans. Interestingly, the canine breed Dachshund is commonly afflicted with disc degeneration and disc herniation in a manner similar to humans (Hoffman and Dow, 2016).…”
Section: Successful Stem Cell Trials In Animalsmentioning
confidence: 99%
“…However, the harsh environment in IDD poses a tremendous challenge for exogenous cell survival due to limited nutrition and inflammatory conditions [22]. Several previous reports have shown that endogenous NPPCs exhibit superior potential in IDD regeneration, with better performance in the degenerated disc environment and better tissue-specific properties with lineage conservation potential [23][24][25][26]. Therefore, it is of critical importance to further elucidate these phenomena.…”
Section: Discussionmentioning
confidence: 99%